Anaerobic batch co-digestion of food waste, septage, and waste cooking oil effect of oil fraction on Methane production and waste stabilization - Amatong, Edgar C. (2012)
Shopping mall restaurants, food processing industries and cafe kitchen generate significant amounts of food waste and used cooking oil. This study explores the application of anaerobic process, which generates methane, a renewable energy resource to food waste coming from this industry. The performance of batch anaerobic co-digestion of food waste, septage and waste cooking oil at varying waste ratio, namely 0, 30, 50 and 70 mass percent volatile solids (VS) was determined. The seed sludge used was a combination of cow rumen obtained from a slaughterhouse and pig manure. The waste mixture that did not contain waste oil yielded the highest amount of methane (61.5 mL.g -1 VS), showed the highest VS destruction (48.51% and rate of hydrolysis (first-order rate constant of 0.187 day-1). Rates of hydrolysis and methane production, methane yield and methane content of the biogas produced were lower at higher amounts of oil added but constant amount of seed sludge. Nevertheless, the hydrolyzed chemical oxygen demand (HCOD) to removed VS ratio indicates that waste oil has been degraded to a certain extent through anaerobic co-digestion. Compared with anaerobic composting, this method of treating food waste is a promising energy-generating option for treating food waste.